Electrosprayed superhydrophobic PTFE: a non-contaminating surface - Burkarter, Ezequiel; Saul, Cyro K.; Thomazi, Fabiano; Cruz, Nilson C. [UNESP]; Zanata, Silvio M.; Roman, Lucimara S.; Schreiner, Wido (Iop Publishing Ltd, 2007)
This paper reports on the exposure of superhydrophobic polytetrafluoroethylene ( PTFE) coatings to common aqueous solutions which are used in biology, biotechnology and chemical sensor applications. Advancing contact angles as high as 173 degrees for aqueous solutions were measured on the PTFE surface. Water drop sliding angles at 2 degrees show a very low contact angle hysteresis. X-ray photoelectron spectroscopy measurements confirm that aqueous solutions can move or stay on the superhydrophobic surface without contamination. Owing to the chemical inertness of the polymer, these results indicate that superhydrophobic PTFE can be used in lab-on-a-chip and multi-sensor devices as well as in biological cultures, where aqueous solutions meet solid surfaces, without contaminating the interface.